Stigma reduction in a disability and mental health programme in Ghana: Lessons in participation - Maria Zuurmond; Augustina Naami; Lyla Adwan-Kamara; Cathy Stephen; Sapana Basnet; Caroline Vanderick; Mohammed Chantimah; Abigail Nana Asamoah; Daisy Macdonald; Crick Lund (African Journal of Disability)
Background: Stigma is a barrier to inclusion for people with disabilities and mental health conditions. There is increasing recognition of the need to address stigma within disability inclusive programmes, but limited research is available on what are effective participatory approaches to stigma reduction interventions.